Prophetic Leadership Study: A Narrative Review on Islamic Banking Institutions - Indra Pratama Putra Salmon; Bambang Agus Diana; Ridho Harta; Jufri Yandes (JURNAL ILMIAH SYI'AR, 2023)
Islamic banking organizations that show two sides of achievement targets, namely economic achievements and socio-religious mission achievements, also bring two consequences, whether they have to lead the organization towards content marketing or carry out only socio-religious missions. In this context, organizational leaders have a strategic role in making Islamic banking institutions capable of optimally achieving their goals. This study aims to explain whether prophetic leadership can balance the current situation with beliefs that are pretty convenient to understand and; see what variables are relevant to the prophetic leadership variable when applied to Islamic banking institutions. This article uses a phenomenon-based foundation in Islamic banking and its governance policies as the object of study. A narrative review of literature studies is the primary approach in writing articles. The study results show that the issue of leadership with prophetic issues has a pattern that follows the specificity of the locus of study (Islamic banking institutions), which indicates that the modern leadership widely displayed in Western literature is not the best. The relevance and superiority of prophetic leadership in maintaining the professionalism and morality aspects of performance to balance economic activities with social activities amid the rapid issue of banking capitalism in Indonesia. Through Maqasid ash-Shariah on, the policies of Islamic banking institutions in Indonesia, prophetic leadership can go hand in hand with business processes and their application to Islamic banking. The implication of this study is to provide an understanding that prophetic leadership, which has been applied long before the emergence of Western leadership models, is still very relevant in dealing with changing times and is opposed to being an alternative to leadership in the modern era like today.